Hematological, Hepatic, and Retinal Phenotypes in Mice Deficient for Prolyl Hydroxylase Domain Proteins in the Liver - Duan, Li-Juan (American Society for Investigative Pathology, 2014)
Prolyl hydroxylase domain (PHD) proteins catalyze oxygen-dependent prolyl hydroxylation of hypoxia-inducible factor 1α and 2α, tagging them for pVHL-dependent polyubiquitination and proteasomal degradation. In this study, albumin Cre (Alb(Cre))–mediated, hepatocyte-specific triple disruption of Phd1, Phd2, and Phd3 (Phd(1/2/3)hKO) promoted liver erythropoietin (EPO) expression 1246-fold, whereas renal EPO was down-regulated to 6.7% of normal levels. In Phd(1/2/3)hKO mice, hematocrit levels reached 82.4%, accompanied by severe vascular malformation and steatosis in the liver. In mice double-deficient for hepatic PHD2 and PHD3 (Phd(2/3)hKO), liver EPO increase and renal EPO loss both occurred but were much less dramatic than in Phd(1/2/3)hKO mice. Hematocrit levels, vascular organization, and liver lipid contents all appeared normal in Phd(2/3)hKO mice. In a chronic renal failure model, Phd(2/3)hKO mice maintained normal hematocrit levels throughout the 8-week time course, whereas floxed controls developed severe anemia. Maintenance of normal hematocrit levels in Phd(2/3)hKO mice was accomplished by sensitized induction of liver EPO expression. Consistent with such a mechanism, liver HIF-2α accumulated to higher levels in Phd(2/3)hKO mice in response to conditions causing modest systemic hypoxia. Besides promoting erythropoiesis, EPO is also known to modulate retinal vascular integrity and neovascularization. In Phd(1/2/3)hKO mice, however, neonatal retinas remained sensitive to oxygen-induced retinopathy, suggesting that local EPO may be more important than hepatic and/or renal EPO in mediating protective effects in the retina.